Effects of Atractylodes macrocephala polysaccharide on growth performance, serum biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) - Wen, Xingxing; Ge, Lingrui; Liu, Kejun; Tan, Shengguo; Hu, Yi (Frontiers in Marine Science, 2024)
The aquaculture industry is tending towards intensification to improve production efficiency and capacity. However, the risk of disease in high-density aquaculture of largemouth bass has increased, requiring strengthened disease prevention and control measures. Studies have shown that Atractylodes macrocephala polysaccharide (AMP) possesses the functions of promoting growth and enhancing immune capacity, and it can be used as a feed additive in animal production. The study aimed to investigate the effects of AMP on the growth performance, serum biochemical indexes and intestinal flora structure of largemouth bass. A total of 360 healthy largemouth bass (mean weight: 15.25±1.29 g) were randomly divided into four groups with three parallel sets in each group. Each group was fed a diet supplemented with 0% (Group D, control group), 0.4% (Group A), 0.8% (Group B), or 1.2% (Group C) AMP for 42 days. The results showed that the addition of an appropriate amount of AMP in the feed could improve the weight gain rate (WGR) and specific growth rate (SGR) of largemouth bass, reduce the feed conversion ratio (FCR), and enhance the growth performance. AMP reduced the levels of AST and ALT, indicating a hepatoprotective effect on largemouth bass, with significant differences from the control group (P < 0.05). AMP also improved the intestinal microbiota composition of largemouth bass, having a positive effect on intestinal health. The analysis of intestinal microbiota revealed that there were 1,288 amplicon sequence variants (ASVs) in the intestine of largemouth bass in Group B, dominated by Firmicutes and Bacteroidota. In contrast, Group C (1.2%) had 920 ASVs, with Fusobacteriota and Firmicutes as the major components, while the relative abundance of Firmicutes was lower, showing significant differences from the control Group D.The functional analysis of intestinal microbiota based on KEGG showed significant differences (P < 0.05) among the four groups in Carbon metabolism, Biosynthesis of amino acids, and Metabolic pathways. Based on comprehensive analysis, the recommended range of AMP addition in the feed is 0.8% -1.2%.